2018
DOI: 10.1016/j.healun.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age, sex, therapeutic intent, race and severity of advanced heart failure on short-term principal outcomes in the MOMENTUM 3 trial

Abstract: This analysis of MOMENTUM 3 suggests that younger age (≤65 years) at implant and pump choice are associated with a greater likelihood of primary end-point success. These findings further suggest that characterization of therapeutic intent into discrete bridge-to-transplant and destination therapy categories offers no clear clinical advantage, and should ideally be abandoned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 22 publications
1
16
1
Order By: Relevance
“…An examination of survival by sex in the ADVANCE BTT+CAP trial showed comparable stroke rates between men and women (11). Similarly, sex had no impact in the six-month endpoint outcomes (including disabling strokes) of the MOMENTUM3 trial (47). Therefore, these results should be interpreted considering the influence of different anticoagulation strategies, implanted devices and patients' compliance over time.…”
Section: Discussionmentioning
confidence: 96%
“…An examination of survival by sex in the ADVANCE BTT+CAP trial showed comparable stroke rates between men and women (11). Similarly, sex had no impact in the six-month endpoint outcomes (including disabling strokes) of the MOMENTUM3 trial (47). Therefore, these results should be interpreted considering the influence of different anticoagulation strategies, implanted devices and patients' compliance over time.…”
Section: Discussionmentioning
confidence: 96%
“…There was no sex difference in stroke risk, but the HeartMate 3 cohort consisted of only 31 women. 54,55 Interestingly, the risk of stroke after 2 years of follow-up was much lower in the HeartMate 3 cohort than the HeartMate II cohort (HR 0.47 [95% CI 0.27-0.84], P=0.02).…”
Section: Adverse Events/complicationsmentioning
confidence: 97%
“…Low pulsatility has been proposed as a major culprit in contributing to these adverse events (Mancini & Colombo, ; Goldstein et al . ). In this CrossTalk proposal, we present the current arguments in favour of maintaining an appropriate amount of arterial pulsatility, in particular in the cerebral circulation, to lower risk in these patients.…”
Section: Schematic Of the Device Location And Components And Typical mentioning
confidence: 97%